Prenatal Diagnosis of Iniencephaly: Clues and Pitfalls - Esin, Sertaç; Yırcı, Bülent; Yalvaç, Serdar; Kandemir, Ömer (Gynecology Obstetrics & Reproductive Medicine, 2012)
Iniencephaly is a congenital malformation consisting of occipital bone defect with enlargement of the foramen magnum, cervical dysraphism and fixed retroflection of the head due to spinal deformities. A 38-years-old woman presented to Etlik Zubeyde Hanim Maternity Hospital perinatology clinic at 18 week of gestation. Ultrasonography revealed a large occipital encephalocele and short cervicothoracic spine. Termination of pregnancy was recommended with the diagnosis of iniencephaly but the family refused it because of religious concerns. She was lost in follow-up but at 38 weeks she presented to our department with regular uterine contractions. Ultrasonography revealed extreme retroflexion of the head, a very short cervicothoracic spine, an encephalocele and marked polyhydramnios. Due to severe retroflexion of the head, a caudal sweep motion of the ultrasound probe gave an impression of a posteriorly placed bladder. Normal chin and neck relation was lacking. A cesarean section was decided due to marked flexion of the spine. A female fetus was delivered weighing 2790 g, with Apgar scores of 1 at 1 min and 1 at 5 min. Iniencephaly is a lethal abnormality which may be diagnosed prenatally with striking ultrasonographic features.